2019
DOI: 10.1371/journal.pone.0217198
|View full text |Cite
|
Sign up to set email alerts
|

The transition from bee-to-fly dominated communities with increasing elevation and greater forest canopy cover

Abstract: Insect pollinator communities are thought to transition from bee-dominated communities at low elevations to fly-dominated communities at high elevations. We predicted that increased tree canopy cover and a subsequent decrease in meadows and flowering plants would limit bees but not flies at higher elevations. We tested and supported this prediction by examining changes in both abundance and species richness for 128 bee species and 96 fly species at key points along an elevational gradient in Northern Arizona r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 51 publications
5
36
0
Order By: Relevance
“…Flies on the other hand are known to be highly abundant at high elevations where other insect taxonomic groups are less represented 14 , 16 , 47 . In our study, there was no significant difference in the abundance and species richness of flies across elevation zones, this may be attributed to the limited range of our mountain (1,640 asl) compared to other studies that have shown distinct variation in the abundance of flies with elevation 14 , 47 . However here, among taxonomic groups, flies and bees were more abundant compared to beetles at the peak elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Flies on the other hand are known to be highly abundant at high elevations where other insect taxonomic groups are less represented 14 , 16 , 47 . In our study, there was no significant difference in the abundance and species richness of flies across elevation zones, this may be attributed to the limited range of our mountain (1,640 asl) compared to other studies that have shown distinct variation in the abundance of flies with elevation 14 , 47 . However here, among taxonomic groups, flies and bees were more abundant compared to beetles at the peak elevation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that global warming could also reduce habitat suitability for key high elevation bee taxa (Wilson et al, 2005), such as Bombus and Megachilidae, and lead to replacement by other low elevation bee taxa. We have found that in this community along the elevation gradient bee communities have a higher turnover in species along the gradient than flies (McCabe et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…This could drive the community patterns since Megachilidae tend to be larger bee species. In general, bee species richness often decreases dramatically with increasing elevation (Inouye & Pike, 1988; Kearns, 1992; Lefebvre et al, 2018; McCabe et al, 2019; McCall & Primack, 1992; Primack, 1978). It has been suggested that the shift from bee dominated pollinator communities to fly dominated communities is primarily due to a greater temperature limitation in bees versus flies (Stone & Willmer, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence upon insect pollination, combined with short foraging distances of generalist fly pollinators, can lead to expectations of higher pollen limitation since the plants must depend on pollen transfer from relatively stochastic and density-dependent pollen vectors [7]. Buffaloberry flowers soon after snowmelt in cooler temperatures and pollen limitation may also be expected in early-blooming and alpine plant species as a result of lower overall pollinator activity in cooler temperatures [10,39,89]. The association between cool temperatures and reduced pollinator activity has led to the cautionary observation that if climate change leads to variations in spring-flowering phenology in early-flowering species, plants may flower at times of restricted pollinator activity, leading to low fruit set and reduction of seedling recruitment [10,90].…”
Section: Pollination Environment and Supplementationmentioning
confidence: 99%